2015
DOI: 10.1186/s12967-015-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

Cell mediated immunity against HPV16 E2, E6 and E7 peptides in women with incident CIN and in constantly HPV-negative women followed-up for 10-years

Abstract: BackgroundVirus-specific cell-mediated immunity (CMI) plays a role in the outcome of genital HPV infections. To cast further light on the question why most women clear their HPV infection while others develop high-grade cervical intraepithelial neoplasia (CIN), we analyzed HPV16 E2-, E6- and E7 -specific CMI in women who developed CIN during a 10-year follow-up of the Finnish Family HPV cohort.MethodsOverlapping 30–35 mer peptides covering the entire HPV16 E2-, E6- and E7 protein sequences were used for defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…This might be an indication of a vanished plasticity of Th17 cells in CIN women [101]. The children born to the CIN mothers had also a cytokine profile distinct from that of the children born to HPV-negative mothers [102, 103]. Our recent unpublished data also indicate that TGF-β levels in the sera of the children born to CIN mothers were significantly higher than those found in the control children.…”
Section: The New Hypothesismentioning
confidence: 95%
“…This might be an indication of a vanished plasticity of Th17 cells in CIN women [101]. The children born to the CIN mothers had also a cytokine profile distinct from that of the children born to HPV-negative mothers [102, 103]. Our recent unpublished data also indicate that TGF-β levels in the sera of the children born to CIN mothers were significantly higher than those found in the control children.…”
Section: The New Hypothesismentioning
confidence: 95%
“…To conclude, HPV‐16‐specific CMI is common in young, sexually inexperienced children, and oral HPV infections are frequently seen in young children. The T‐helper 2 cell cytokine profile might also predispose to persistent oral HPV‐16 infection in women . We recently showed that the HLA‐G allele concordance might affect the vertical transmission of HPV, especially to the oral cavity .…”
Section: Hpv and Immunitymentioning
confidence: 99%
“…However, it remains incompletely understood why there is apparent failure of the immune system in otherwise healthy individuals to clear warts for months or years. Among these individuals, viral warts do not respond to conventional therapies or they recur soon after destructive procedures and persist for months and years …”
Section: Introductionmentioning
confidence: 99%
“…Among these individuals, viral warts do not respond to conventional therapies or they recur soon after destructive procedures and persist for months and years. 3 Interleukin 17 (IL-17) is a pro-inflammatory cytokine involved in the control of many different disorders that include autoimmune, oncogenic, and many infectious diseases. 4 T cells that produce IL-17 arise as a specific population of CD4-positive T cells, which are called T helper 17 (Th17) cells that are distinct from the classic Th1 and Th2 cells.…”
Section: Introductionmentioning
confidence: 99%